Design Application Performance Monitoring Salesman In the Sales Department at CV. MULTI BUSINESS MANADIRI - Agatra, Chandra; Martono, Siswo; lemantara, julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Monitoring the performance of Salesman at the distributor company is one of the important factors to note the company, from the good performance of the salesman, the company can increase the target of selling. Not only the performance of salesmen, but the data storage customers also become important for companies distributor. Storage of data managed and controlled performance of salesmen and direct the sale corresponding region can increase the company's sales target But the process of monitoring the performance of salesmen, good data storage and directed sales to the salesman has not been applied to CV. Multi Usaha Mandiri resulting CV. Multi Usaha Mandiri can not meet sales targets.To fix these problem then make monitoring application performance salesman. This application can store customer data, direct the sale area in accordance with the sales of each customer and can monitor the performance of salesmen. With this application can help CV. Multi Usaha Mandiri in managing customer data, monitoring the performance of salesmen and direct the sale area according to sales reports.